Respostas de híbridos de meloeiro amarelo à salinidade da água de irrigação - Campelo, André Rufino (2017)
The objective of this study was to evaluate the response of three hybrids of yellow melon (Natal, Goldex, Iracema) irrigated with saline water in the following conductivites (0.5, 1.5, 3.0, 4.5, 6.0 dS m-1). The experiment was conducted at the Experimental Field of Embrapa Agroindústria Tropical, Pacajus, Ceará. A randomized complete block design was used in subdivided plots 3 x 5, with 4 replications, totaling 60 plots. During the plant growth cycle, the gas exchanges (photosynthesis, stomatal conductance and transpiration) were evaluated, and one plant per plot was collected at 39 and 66 days after sowing (DAS) to growth analysis. At the end of the experiment were evaluated the leaf area and the dry matter of stems and leaves of the collected plants. After these analyzes, the levels of sodium, potassium, chloride and carbohydrates of the leaves and stems were determined. In addition, the following fruits characteristics were evaluated: weight, number of fruits, length and diameter, shell and pulp thickness, length and diameter of the internal cavity, soluble solids content and titratable acidity. Finally, with the production data the productivity of the plants was estimated, as well as the degree of tolerance to salinity of each hybrid was determined. Plant growth was reduced by increased salinity of irrigation water, with the hybrid Iracema being the most affected. Gaseous exchanges were reduced by salinity in all evaluated periods, with the hybrid Natal presenting the highest values of photosynthesis. The reductions in gaseous exchange and plant growth resulted from increased chloride and sodium contents and reduced potassium contents in leaves and stems observed in all the evaluation periods. Foliar carbohydrates were increased with increasing salt concentration of irrigation water up to 39 DAS, at 66 DAS a reduction in the amount of foliar carbohydrates was observed. The hybrids Goldex and Natal presented larger and heavier fruits than Iracema, while the latter presented a larger number of fruits. Goldex produced the sweetest fruits, while the fruits of Iracema were more acidic. The productivity decreased with increasing irrigation water salinity, with no differences between hybrids. The hybrid Natal was the most tolerant to salinity, followed by the hybrid Iracema, and finally the hybrid Goldex.